Pendekatan Psikologis dalam Meningkatkan Kesadaran Diri dan Motivasi Belajar: Perspektif dan Implikasi Islam - Siti Maskanah; Evita Yuliatul Wahidah; Husnan Sulaiman (La-Tahzan: Jurnal Pendidikan Islam, 2024)
Building self-awareness is very important for us so that we can increase motivation in learning because in Islam learning is a human obligation throughout his life. Self-awareness is something that is very important for everyone. Someone who has self-awareness can certainly actualize their desires in their life. Awareness The importance of education in Islam will be able to motivate everyone to increase their potential and through continuous education they will be able to become human beings who are useful for the nation, state and religion. This research is a type of library research, namely by reading references from journals. and related books. The results of this research explain that self-awareness is very important and must be present in everyone so that someone can increase their motivation to learn. Because in Islam humans are required to continue to seek knowledge. So as a good Muslim you must have a high enthusiasm for learning. and full of attention in exploring and seeking quality knowledge. So that he can continue to develop his potential and be able to achieve happiness in this world and the hereafter.